The performance of hydrogen-powered 4-stroke SI engine using locally designed fuel regulator - Yamin,Jehad Ahmad (2010)
In this work, the performance of a spark ignition engine powered with hydrogen fuel was studied and compared with gasoline fuel. Hydrogen fuel was used, using a locally made stainless steel gaseous regulator which was designed and installed in engine. This regulator was located between the engine and the hydrogen fuel cylinder, and it is triggered by the suction pressure and hence it keeps the fuel supply lines open under negative pressure only, which exists under no leak conditions and when the engine is running. It was found that the engine runs smoothly with the regulator in place. Further, it was found that the brake power and the volumetric efficiency of the engine drop down when the engine is powered by hydrogen, while the specific fuel consumption is drastically improved (by almost one-third) when hydrogen is used as a fuel. Finally, the thermal efficiency remains almost the same in both cases of fuels.